Predictors of mortality after admission to pediatric intensive care unit in oncohematologic patients without history of hematopoietic stem cell transplantation: A single‐center experience. Issue 10 (28th June 2019) - Pillon, Marta; Sperotto, Francesca; Zattarin, Emma; Cattelan, Manuela; Carraro, Elisa; Contin, Anna E.; Massano, Davide; Pece, Federico; Putti, Maria C.; Messina, Chiara; Pettenazzo, Andrea; Amigoni, Angela
Abstract: Background: Pediatric oncohematologic patients are a high‐risk population for clinical deterioration that might require pediatric intensive care unit (PICU) admission. Several studies have described outcomes and mortality predictors for patients post hematopoietic stem cell transplantation (HSCT), but fewer data exist regarding the category of non‐HSCT patients. Procedure: All oncohematologic non‐HSCT patients ≤18 years requiring PICU admission from 1998 to 2015 in our tertiary‐care academic hospital were retrospectively evaluated by means of the pediatric hematology‐oncology unit database and the Italian PICUs data network database. We assessed the relation between demographic and clinical characteristics and 90‐day mortality after PICU admission. Results: Of 3750 hospitalized oncohematologic patients, 3238 were non‐HSCT and 63 (2%) of them were admitted to the PICU. Patients were mainly affected by hematological malignancies (70%) and mostly were in the induction‐therapy phase. The main reasons for admission were respiratory failure (40%), sepsis (25%), and seizures (16%). The median PICU stay was 5 days (range 1‐107). The mortality rate at PICU discharge was 30%, and at 90 days it was 35%. Fifty‐five percent of deaths happened in the first 2 days of the PICU stay. Cardiac arrest ( P = .007), presence of disseminated intravascular coagulation (DIC, P = .007), and acute kidney injury (AKI) at PICU admission ( P < .001) and during PICU stay ( P = .021) were significant predictors of mortality in the multivariate analysis. Respiratory failure and mechanical ventilation were not associated with mortality. Conclusions: A relatively small percentage of non‐HSCT patients required PICU admission, but the mortality rate was still high. Hemodynamic instability, DIC, and AKI, but not respiratory failure, were significant predictors of mortality.